Unio Non Confusio: Sebuah Upaya Menganalisis Gagasan Aktivitas (Energeia) dan Persatuan Dwinatur Kristus dalam Kaitannya dengan Persatuan Mistik - Kuganda, Dandy; Lumbanbatu, Kornelius (Veritas : Jurnal Teologi dan Pelayanan, 2023)
This article expounds on the hypostatic union of Christ in its relation to Lutheran and Reformed theology. We begin by contemplating an ontological problem in recent discourse on Martin Luther’s and John Calvin’s conception of mystical union. Both sides believed that humanity is united with Christ in faith to receive His benefits, i.e., justification and sanctification. However, none of them explicates how such a union can distribute the benefits of Christ without confusing the divine nature and human nature. Therefore, we argue that the synergy (Gk. syn- [συν-] + energeia [ἐνέργειᾰ]) in Christ’s hypostatic union is the ontological basis for the participation of humanity into the divine activity of Christ. We defend this argument with a twofold explanation that is constructed using the analytic qualitative method that is executed through a library research. The first part contains a description and analysis of the doctrine of hypostatic union in the patristic era. The second part contains an exploration of the concept of activity (Gk. energeia) in the tradition of Eastern Christianity and its correlation to the participation of humanity into the divine activity of Christ. Lastly, we complete this twofold explanation by referring to the Eucharist as the concrete locus of a continuous mystical union.